ANALISIS PREFERENSI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA TOMORO COFFEE KOTA BOGOR - Elfa Syukrina; Marcella Magdhalena Erlely; Salsa Nur Maulida; Muhammad Ifran; Veralianta Br Sebayang; Tasya Angelita (Jurnal Ekonomi dan Bisnis (EK dan BI), 2024)
Tomoro Coffee is one of the local coffee shops that is growing rapidly in Indonesia. Understanding consumer preferences for Tomoro Coffee is important for business development and effective marketing strategies. This research aims to analyze consumer preferences regarding Tomoro Coffee purchasing decisions using descriptive analysis and the Fishbein multi-attribute model with a total of 100 respondents who are Tomoro Coffee consumers. The research results show that the factors that consumers prioritize in determining purchases are the taste and service attributes, while the location and packaging attributes do not have much influence on purchasing decisions. This research provides important implications for Tomoro Coffee to maintain and improve product quality, improve service, create a comfortable atmosphere, and expand the reach of shop locations. Understanding consumer preferences can help Tomoro Coffee make marketing strategy decisions to increase competitiveness and achieve business success.